Report on research in Lesotho - Wells, Robin (International Library of African Music, 1992)
Like many aspects of life in Lesotho, the indigenous music is caught up in a process of rapid and fundamental change, and as Hugh Tracey noted in his report on a recording tour of Basutoland (Lesotho) in 1959, there is a "steady decline" in "original musicmaking". But music, like any aspect of culture, is constantly in a state of flux. As old forms disappear, so new ones evolve to suit the new lifestyles and demands of society. The urge to make music is always present - it merely adapts itself to suit the ever-changing environment.
Keywords: African Music; Lesotho